Madrid's forgotten avant-garde : between essentialism and modernity - Schammah Gesser, Silvina (Sussex Academic Press, 2015)
Madrid's Forgotten Avant-Garde explores the role played by artists and intellectuals who constructed and disseminated various competing images of national identity that polarized Spanish society prior to the Civil War. The convergence of modern and essentialist discourses and practices, especially in literature and poetry-in what is conventionally called in Spanish letters the Generation of '27-created fissures between competing views of aesthetics and ideology that cut across political affiliation. Author Silvina Schammah Gesser exposes the paradoxes facing Madrid's cultural vanguards, as the.
Keywords: Literature, Experimental -- Spain -- History and criticism.; Avant-garde (Aesthetics) -- Spain -- Madrid -- History -- 20th century.; Literature and society -- Spain -- Madrid -- History -- 20th century.; Madrid (Spain) -- Intellectual life -- 20th century.; Littérature expérimentale -- Espagne -- Histoire et critique.; Littérature et société -- Espagne -- Madrid -- Histoire -- 20e siècle.; LITERARY CRITICISM -- European -- Spanish & Portuguese.; Avant-garde (Aesthetics); Intellectual life; Literature and society; Literature, Experimental; Spain; Spain -- Madrid; 1900-1999; Criticism, interpretation, etc.; History